Environmental & architectural phenomenology. Vol. 19, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 2008)
Vol. 19, No. 2, Spring 2008 (includes "items of interest," course syllabus of Dylan Trigg's "From Airports to Asylums", essay by Matt Thompson, and extracts from architect Ron Walkey).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals